Factors Affecting Disclosure of Islamic Social Reporting on Companies Listed In Jakarta Islamic Index 2017-2019 - Purnama Putra; Rika Aryanti (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to determine the effect of company size, profitability, Islamic securities, liquidity and leverage on the disclosure of Islamic Social Reporting in companies listed on the Jakarta Islamic Index (JII) for the 2017-2019 period. The data used are the financial statements of companies listed on the Jakarta Islamic Index during the 2017-2019 period. Data were analyzed using multiple linear regression. The sample in this study were 17 companies that were consistently listed on the Jakarta Islamic Index for the 2017-2019 period. Samples were taken using purposive sampling technique. This study indicate that company size has a significant positive effect, profitability, Islamic securities liquidity and leverage have no significant positive effect on the disclosure of Islamic social reporting. Meanwhile, simultaneously company size, profitability, Islamic securities, liquidity and leverage have a significant positive effect on the disclosure of Islamic social reporting.